Improving the Performance of Titanium Oxide Nanocomposites as NO2 Gas Sensors for Optimum Sensitivity - Nemea, Ameer A.; Al-Abdaly, Basim I. (Iraqi Journal of Science, 2024)
In this study, we investigate the performance improvement of titanium oxide (TiO2) nanocomposites as NO2 gas sensors for optimum sensitivity. The TiO2 nanocomposites were synthesized using a solvothermal method and were modified with different dopants and additives to enhance their sensing properties. The sensing performance of the TiO2 nanocomposites was evaluated in terms of sensitivity, selectivity, response time, and recovery time. The synthesized nanocomposites were successfully characterized using AFM, FTIR, SEM-EDX and XRD techniques. The results showed that the addition of additives such as TiO2/GO, TiO2-Ag/GO and TiO2- Al2O3/GO: TiO2/GO significantly improved the sensing properties of the TiO2 nanocomposites. The Ag-doped TiO2 nanocomposites exhibited the highest sensitivity towards NO2 gas with a very low detection limit. The Al2O3-doped TiO2 nanocomposites showed good selectivity towards NO2 gas compared to other interfering gases and has led to increase in the surface area. In conclusion, the addition of additives and the optimization of the annealing temperature can significantly improve the sensing properties of TiO2 nanocomposites towards NO2 gas. The findings of this study can contribute to the development of highly sensitive and selective NO2 gas sensors for various applications such as environmental monitoring and industrial safety.